A mixed methodology for detailed 3D modeling of architectural heritage - Arce, D (2016)
Architectural and archaeological heritage is the most representative part of history of a country. For these reasons, over the years, the scientific community has focused its attention on three-dimensional (3D) modeling techniques, conservation, structural analysis and other related applications. Laser scanning, shape from structured light, shape from silhouette, shape from video and shape from photometry are among the techniques that have been used over the past years for 3D modeling of archeological heritage. The application of 3D modeling can be found in several disciplines. In Architecture, it is used to generate digital models from which drawings can be produced. Aerial and terrestrial photogrammetry Photogrammetry is commonly used for digitization of 3D models in different applications due to the fast acquisition process and low cost of equipment. Digitization of structures with terrestrial laser scanner requires the usage of a correct methodology in order to generate a complete 3D model.